Dispersion compensation of optical systems utilizing fiber Bragg grating at 15 Gbits/s - Alaa Hussein Ali; Saad Mutashar; Ali Mahdi Hammadi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Nowadays the technological advancement of the information transmission is developing very rapidly and it becomes necessary to achieve a high speed in the transmission of data as well as higher data rate. Developments in optical communication systems address these needs. However, despite all the features and advantages of optical communication systems, the dispersion is still the main challenges. In this paper and to this end, fiber Bragg grating (FBG) is used in order to overcome the dispersion issue in the wavelength division multiplexing (WDM) transmission system. The WDM transmission system is simulated using the advanced tools of Optisystem 13. The simulation program was used at a speed of 15 Gbits/s with 50Km optical fiber length based on the different input design parameters such as input signal power, optical fiber length and attenuation coefficient. In addition, the output performance parameters are discussed in terms of quality factor (Q-factor) and eye diagram. Moreover, a comparison between the proposed design and previous related works is presented.